The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1477-2574.2010.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of electrosurgical vessel-sealing devices in biliary tract surgery in a porcine model

Abstract: Given the high rates of failure of the EBVS device and the shears in consistently sealing biliary ducts, we do not recommend their routine use in biliary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…The burst pressure setup, consisting of a pressure meter (Model 717 100 G, Fluke, Everett, Washington), infusion pump (Cole Parmer, Vernon Hills, Illinois), and an iris clamp is a standard method for measuring vessel seal burst strength 24,25 and is shown in Fig. 3.…”
Section: Burst Pressure Measurementsmentioning
confidence: 99%
“…The burst pressure setup, consisting of a pressure meter (Model 717 100 G, Fluke, Everett, Washington), infusion pump (Cole Parmer, Vernon Hills, Illinois), and an iris clamp is a standard method for measuring vessel seal burst strength 24,25 and is shown in Fig. 3.…”
Section: Burst Pressure Measurementsmentioning
confidence: 99%
“…None of the cystic ducts sealed with the VSD leaked at the cut surface of the duct. Previous studies using different animal models for cystic duct and common bile duct closure with vessel sealant devices have conflicting results . The seal failure that occurred in the study from Matthews et al used the first generation of vessel sealant device whereas we used the newer generation with a different algorithm for the measurement of impedance.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to draw conclusions from the study because of the variability in species and tissue type (cystic duct versus common bile duct). We also used a 10 mm VSD whereas other studies that reported leakage used a 5 mm sealant device . The seal dimensions for the 10 mm Atlas hand piece are 22 mm in length and ∼2.5 mm in width (after cut; personal communication, Heard D, Covidien, April 2013) whereas the seal dimensions for the 5 mm hand piece by Hope et al are 18 mm in length and 1–1.8 mm in width (after cut) leaving a substantially smaller seal width behind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vessel burst pressure measurements are considered a standard method for measuring vessel seal strength 26,29,31 and was, therefore, used as the primary indicator of success for this study. The burst pressure setup consisted of a pressure meter (Model 717 100 G, Fluke, Everett, Washington), infusion pump (Cole Parmer, Vernon Hills, Illinois), and an iris clamp.…”
Section: Burst Pressure Measurementsmentioning
confidence: 99%